Differences in Decision-Making Behavior Between Elite and Amateur Team-Handball Players in a Near-Game Test Situation - Hinz, Matthias; Lehmann, Nico; Aye, Norman; Melcher, Kevin; Tolentino-Castro, J. Walter; Wagner, Herbert; Taubert, Marco (Frontiers in Psychology, 2022)
Athletic features distinguishing experts from non-experts in team sports are relevant for performance analyses, talent identification and successful training. In this respect, perceptual-cognitive factors like decision making have been proposed to be important predictor of talent but, however, assessing decision making in team sports remains a challenging endeavor. In particular, it is now known that decisions made in comparably simple and reductionistic laboratory settings differ from those actually made in on-field situations. To address this point, our study compared elite and amateur players’ decision-making behavior in a close-to-real-world environment including sport-specific sensorimotor responses. Team-handball players (N = 44) were asked to respond as quickly as possible to representative, temporally occluded attack sequences in a team-handball specific defense environment on a contact plate system. Specifically, participants had to choose and perform the most appropriate out of four prespecified, defense response actions. The frequency of responses and decision time were used as dependent variables representing decision-making behavior. We found that elite players responded significantly more often with offensive responses (p < .05, odds ratios: 2.76 - 3.00) in left-handed attack sequences. Decision time decreased with increasing visual information, but no expertise effect was found. We suppose that expertise-related knowledge and processing of kinematic information led to distinct decision-making behavior between elite and amateur players, evoked in a domain-specific and near-game test setting. Results also indicate that the quality of a decision might be of higher relevance than the required time to decide. Findings illustrate application opportunities in the context of performance analyses and talent identification processes.